(untitled) - Hadfield, Jill (London, 1999)
A wide variety of games including puzzles, role-play, board games and guessing *Each game involves vocabulary memorisation, personalisation, then communication *Teacher's notes help you manage each game
Keywords: English language,English language,Ngôn ngữ tiếng Anh,Ngôn ngữ tiếng Anh; Vocabulary,Từ vựng